Theoretical study of charge transport properties of a Si(DPP)2 complex - Bimukhanov, A.N.; Aldongarov, A.A. (Recent Contributions to Physics, 2022)
This article provides a study of the calculations of charge transport, reorganization energy, intermolecular transfer integral and charge mobility for the optimized structure of the new neutral hexacoordinated silicon complex Si(DPP)2. The main calculated and experimental geometric data on the optimized structure are also presented. The complex has a distorted octahedral geometry with short Si-N bond lengths averaging: calculated - 1.958365 Å and experimental - 1.9111 Å. The Si(DPP)2 structure contains two diphenylpyridine (DPP = 2,6-diphenylpyridine ligand) ligands. Optimization and computational calculations of the necessary data of charge transport were performed using a B3LYP functional and a 6-31G* basis set. Geometrical parameters for structure optimization were obtained from recent, known, experimental data. The obtained theoretical data on the charge transport of the Si(DPP)2 structure were compared with the known experimental data. Based on a comparison of the theoretical and experimental values for the charge transport properties of the Si(DPP)2 compound, it was shown that the method we used for calculating the charge mobility gives relatively close values. This work shows that computational methods can help in the further study of future structures, as well as predict the future parameters of as yet unexplored silicon complexes.